"Should I stay or should I go?" Exploring the influence of individual factors on attachment, identity and commitment in a post-socialist city. (July 2020) - Tournois, Laurent; Rollero, Chiara
Abstract: Although literature suggests that high attached and identified individuals are more prone to cooperate and remain in their environment, the influence of place attachment and place identity on place commitment has not been investigated yet. The main purpose of the present study was to assess such influence. Questionnaires were administered to residents ( n  = 466) in the city of Belgrade, a post-socialist context which is largely understudied in prior research. The effect of socio-demographic characteristics that may predict place attachment and place identity was examined as well. Results showed that both place attachment and place identity were strongly associated with place commitment. Elderly people revealed higher levels of attachment and identity, whereas low educated individuals scored higher only on place identity. Surprisingly, participants born in Belgrade scored lower on attachment and identity. Findings are discussed in the light of the peculiar situation of the context, i.e., the capital city of a post-socialist country (Serbia) which had to face very significant changes in the last thirty years. Significant implications for policy makers and academics are underlined. Highlights: Both place attachment and place identification predicted place commitment. Age was positively associated with both attachment and identification. Educational level was negatively related to place identification. Place of birth was negatively associated with both attachment and identification. Results emphasize the need to consider the peculiarities of a post-socialist context.